Antibacterial Activity of Kasturi Orange (Citrus microcarpa Bunge) to Inhibit Propionibacterium acnes - Mayasari, Ulfayani; Novita, Fanny; Sapitri, Alfi; Nasution, Rizki Amelia (International Conference on Sciences Development and Technology, 2021)
Kasturi orange (Citrus microcarpa Bunge) is one of the plants that can be used as medicine, for example to treat coughs, itching or body odor removal. The purpose of this study was to determine whether Kasturi oranges were able to inhibit the growth of Propionabacterium acnes bacteria that causes acne. The research method used is experimental. The experiment consisted of 4 treatments and three repetitions. The results showed that the diameters of the inhibition zones obtained by lime juice at concentrations of 25%, 50%, 75%, 100% were 3.86 mm, 7.13 mm, 9 mm, 11.1 mm. Based on the results obtained, it can be concluded that Kasturi orange juice is able to inhibit the growth of the Propionibacterium acnes bacteria.